Pendekatan Pastoral Konseling Model Dalam Menangani Anak Berkebutuhan Khusus Dalam Perspektif Filipi 4:13 - Inez Suantika Saleleu; Marisa Aulia Gea (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This study reviews the pastoral counseling model approach in dealing with children with special needs using the perspective of Philippians 4:13. In this study the author uses a descriptive qualitative approach with a literature study method. Children with special needs refer to children who face various forms of physical, mental, emotional or learning limitations. In this context, a pastoral counseling approach is applied with the principle that everything can be borne through God-given strength. A deep understanding of the condition of children with disabilities, a holistic approach that pays attention to physical, emotional, mental and spiritual aspects, and self-strengthening through spiritual beliefs are the main focus in dealing with children with disabilities. The conclusion of this study confirms that the pastoral counseling approach in the context of Philippians 4:13 provides a solid foundation in guiding and supporting children with disabilities, emphasizing the integration of spiritual beliefs, holistic understanding of the child's condition, and providing comprehensive support. This research encourages educational practitioners to carry out their roles with sincerity and humility, and to pay attention to the needs and development of children with special needs.